ANALISIS STRATEGI PEMASARAN RUMAH BATIK SAMPAN PESONA MINANG DALAM UPAYA MENINGKATKAN VOLUME PENJUALAN - Erniwati, Erniwati; Safardi, Safardi; Yuhada, Reva Dara (Universitas Sumatera Barat, 2024)
The implementation of marketing strategies greatly influences company performance. The success or failure of a company is largely determined by how the company develops to be able to compete in winning consumers by implementing effective marketing strategies, namely: Increasing quality products, Improving strategic locations, Maximizing product promotions. The research results show that based on the development of the SWOT Matrix Diagram analysis, Rumah Batik Sampan Pesona Minang needs to develop a SO (Strength and Opportunities) Strategy. From processing the questionnaire, the results obtained are that the Company's position at point X is in quadrant I, where the Company has enough strength to take advantage of the opportunities available. By paying attention to the proximity of point X to quadrant IV, where threats are sufficient to put pressure on the Company in competition. Rumah Batik Sampan Pesona Minang improves its competitive strategy by providing quality products, increasing employee skills in batik, increasing promotions, increasing cooperation between fellow businesses, improving strategic locations, increasing business networks, increasing stock of goods and anticipating product price variations.